2009
DOI: 10.1021/ol900783m
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Conformationally Constrained cis-Amide Hsp90 Inhibitors

Abstract: Conformationally constrained CIS-amide chimeric inhibitors of Hsp90 have been synthesized and evaluated for their Hsp90 inhibitory activity. These new compounds exhibited Hsp90 ATPase inhibition and induced Hsp90-dependent client protein degradation in a dose-dependent manner. Biological data reported herein suggests that amide bond isomerization of geldanamycin derivatives plays an important role in affinity for the heteroprotein complex present in cancer cells.The 90 kDa heat shock proteins (Hsp90) are ATP-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…However, a recent study concluded that no isomerization step occurs in the binding of the benzoquinone ansamycins to Hsp90 (Onuoha et al, 2007) and proposed that small quantities of the cis-amide isomer in solution, identified in an NMR study (Thepchatri et al, 2007), may bind directly to Hsp90, and in vivo potency could be due to the direct binding of the hydroquinone of the cis-amide isomer. This counters the results of a study examining the effects of conformationally constrained cis-amide chimeric inhibitors of Hsp90 (Duerfeldt et al, 2009) and our molecular docking studies in which the cis-amide isomer would not dock into NQO1. However, the results of a binding affinity study using BODIPY-geldanamycin in the absence and presence of reducing agents reported by Onuoha et al may, in fact, support Hsp90-mediated isomerization.…”
contrasting
confidence: 98%
See 1 more Smart Citation
“…However, a recent study concluded that no isomerization step occurs in the binding of the benzoquinone ansamycins to Hsp90 (Onuoha et al, 2007) and proposed that small quantities of the cis-amide isomer in solution, identified in an NMR study (Thepchatri et al, 2007), may bind directly to Hsp90, and in vivo potency could be due to the direct binding of the hydroquinone of the cis-amide isomer. This counters the results of a study examining the effects of conformationally constrained cis-amide chimeric inhibitors of Hsp90 (Duerfeldt et al, 2009) and our molecular docking studies in which the cis-amide isomer would not dock into NQO1. However, the results of a binding affinity study using BODIPY-geldanamycin in the absence and presence of reducing agents reported by Onuoha et al may, in fact, support Hsp90-mediated isomerization.…”
contrasting
confidence: 98%
“…The intrinsic structural properties of the ansamycin ring, the anchoring of the carbamate through interaction with Asp90 at the base of the nucleotide-binding domain, and the interaction of the ansa ring with amino acid residues via through-bond interactions with the specific solvent network in the nucleotide-binding domain may also aid to drive trans-cis isomerization (Pappenberger et al, 2001). The confirmation of Hsp90-mediated trans-cis isomerization of the benzoquinone and hydroquinone ansamycins is important because it could be exploited in the development of new Hsp90 inhibitors, and the effect of conformationally restrained cis-amide isomers of benzoquinone ansamycin analogs on Hsp90 inhibition has been reported (Duerfeldt et al, 2009).…”
mentioning
confidence: 99%
“…Geldanamycin may have adverse effects due to the reactive epoxide moiety and other adverse structural features [72]. A chimeric structure containing quinone moiety from geldanamycin and resorcinol from radicicol gave rise to radamide, a molecule with higher affinity for GRP94 and antiproliferative activities on various cancer cell lines [73,74]. The flavonol apigenin also led to a reduction in GRP94 expression in ER stressed cells [58].…”
Section: Er Chaperone Modulatorsmentioning
confidence: 99%
“…These molecules show low-micromolar inhibitory activity against purified Hsp90 (1 .5 mm, ATPase assay) and a~10fold increase in cellular activities against MCF7 and SKBr3 cancer cells with respect to the lead compound, radamide. [39] In a subsequent study, Lee and collaborators used quantum chemical calculations and mutagenesis experiments to propose that the trans/cis isomerization of GA was induced by Hsp90, and identified Ser 113 as a key residue involved in the catalysis of this conversion. [40] Conversely, using ITC binding assays Onuoha et al did not observe a dramatic reduction in binding affinity for the S113A mutant with respect to the wild-type protein, suggesting that Hsp90 does not catalyze the ligand isomerization.…”
Section: Nt Inhibitorsmentioning
confidence: 99%